A revision of European species of the genera Melanagromyza Hendel and Hexomyza Enderlein, with a supplement on the genus Ophiomyia Braschnikov (Diptera: Agromyzidae). - Spencer, Kenneth Angus (Contributions to Entomology = Beiträge zur Entomologie, 1966)
All Palaearctic species described in or subsequently transferred to the genus Melanagromyza Hendel have been examined. On the basis of this study the generic concept of Melanagromyza has been restricted and the genus Hexomyza Enderlein is revived witli amended concepts. Twenty-five species are now included in Melanagromyza, including four new species, and for these an entirely new key is given. Four gall-causing species are included in Hexomyza. In a Supplement to the author's recent (1964) Revision of Ophiomyia species three new species are described, four further species are transferred to Ophiomyia from Melanagromyza and three new synonomies are established. Illustrations are given of the male genitalia of all but two species, of which only the female is known. Nomenclatural Actssquamata Becker, 1903 (Agromyza), syn. n. of Melanagromyza sojae (Zehntner, 1900)salicis (Malloch, 1913) (Hexomyza), comb. n. hitherto Agromyza salicisschineri (Giraud, 1861) (Hexomyza), Lectotype; comb. n. hitherto Agromyza schinerisimplicoides (Hendel, 1920) (Hexomyza), Lectotype; comb. n. hitherto Melanagromyza simplicoidesaenea (Meigen, 1830) (Melanagromyza), Lectotype described as Agromyza aeneaalbocilia Hendel, 1931 (Melanagromyza), Lectotypececidogena Hering, 1927 (Melanagromyza), syn. n. of Hexomyza salicis (Malloch, 1913)cunctans (Meigen, 1830) (Melanagromyza), Lectotype described as Agromyza cunctanseuphorbiae Hendel, 1923 (Melanagromyza), syn. n. of Ophiomyia beckeri (Hendel, 1923)ferulae (Spencer, 1966) (Melanagromyza), spec. n.goniaea Hendel, 1931 (Melanagromyza), syn. n. of Ophiomyia beckeri (Hendel, 1923)knautiae Hering, 1944 (Melanagromyza), syn. n. of Ophiomyia longilingua (Hendel, 1920)multiseta Rydén, 1949 (Melanagromyza), syn. n. of Melanagromyza lappae (Loew, 1850)nitens Rohdendorf-Holmanová, 1958 (Melanagromyza), syn. n. of Melanagromyza lappae (Loew, 1850)paracelsus Hering, 1933 (Melanagromyza), syn. n. of Ophiomyia orbiculata (Hendel, 1931)rohdendorfi Spencer, 1966 (Melanagromyza), spec. n.siciliensis Spencer, 1966 (Melanagromyza), spec. n.submetallescens Spencer, 1966 (Melanagromyza), spec. n.fuscociliata Hendel, 1931 (Melanagromyza aeneiventris), syn. n. of Melanagromyza aenea (Meigen, 1830)dianellae (Kleinschmidt, 1961) (Ophiomyia), comb. n. hitherto Melanagromyza dianellaeimprovisa Spencer, 1966 (Ophiomyia), spec. n.inaequabilis (Hendel, 1931) (Ophiomyia), Lectotype; comb. n. hitherto Melanagromyza inaequabilislongilingua (Hendel, 1920) (Ophiomyia), Lectotype; comb. n. hitherto Melanagromyza longilinguaononidis Spencer, 1966 (Ophiomyia), spec. n.paramonovi Spencer, 1963 (Ophiomyia), comb. n. hitherto Melanagromyza paramonovirostrata (Hendel, 1920) (Ophiomyia), Lectotype; comb. n. hitherto Melanagromyza rostratasimplex (Loew, 1869) (Ophiomyia), comb. n. hitherto Agromyza simplexsuavis Spencer, 1966 (Ophiomyia), spec. n.